2000
DOI: 10.1557/jmr.2000.0114
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and nanoindentation behavior of a bulk Zr–Al–Ti–Cu–Ni amorphous alloy

Abstract: The crystallization and nanoindentation behavior of a Zr–10Al–5Ti–17.9Cu–14.6Ni (at.%) bulk amorphous alloy (BAA) were studied. Resulting from the kinetic nature of phase transformation in multicomponent alloys, the crystallization path is complex. Despite the complexity of different crystallization paths, the main final crystallized product in the Zr-based BAA is Zr2Cu. Young's modulus and hardness of the BAA were found to increase with an increase in annealing temperature. The observed mechanical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
58
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(83 citation statements)
references
References 29 publications
15
58
1
Order By: Relevance
“…[33][34][35][36][37][38] Inoue et al, in the study on the Zr 65 Cu 27:5 Al 7:5 metallic glass, showed that crystallization takes place through the precipitation of a body-centered tetragonal (bct) Zr 2 Cu phase (a ¼ 0:322, and c ¼ 1:12 nm), in which Al atoms are presumably dissolved. 33) They also showed that the morphology of crystallized structures strongly depends on the annealing temperature: above T g it exhibits a dendric morphology, while below T g it shows a more smooth morphology.…”
Section: Crystallization Behaviormentioning
confidence: 99%
“…[33][34][35][36][37][38] Inoue et al, in the study on the Zr 65 Cu 27:5 Al 7:5 metallic glass, showed that crystallization takes place through the precipitation of a body-centered tetragonal (bct) Zr 2 Cu phase (a ¼ 0:322, and c ¼ 1:12 nm), in which Al atoms are presumably dissolved. 33) They also showed that the morphology of crystallized structures strongly depends on the annealing temperature: above T g it exhibits a dendric morphology, while below T g it shows a more smooth morphology.…”
Section: Crystallization Behaviormentioning
confidence: 99%
“…From its introduction in the early nineties, Zr-based bulk metallic glass has attracted much attention due to its unique properties, such as superior strength (up to 2 GPa), high elastic strain limit (~2%), relatively low Young's modulus (50-100 GPa), excellent corrosion resistance and improved wear resistance (Bruck et al, 1994;Gilbert et al, 1997;Inoue, 1995;Johnson, 1999;Liu et al, 2005;Pang et al, 2000;Wang et al, 2000). Due to its thermal stability and excellent mechanical properties, it is no wonder that such material is gaining popularity in various engineering fields, such as in biomedical applications (Liu et al, 2007) and in structural applications in irradiation rich environments (Shah et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…4) One of the topics often highlighted by nanoindentation studies on BMGs is the inhomogeneous plastic flow observed during indentation experiments. Since Wang et al 5) reported a few small discrete steps (so-called 'pop-ins') in nanoindentation loaddisplacement (P-h) curves of Zr-Al-Ti-Cu-Ni BMG, many works have been focused on the unique feature of the 'popins' and 'serrations' in loading curve of the BMGs during nanoindentation. [6][7][8][9][10][11][12][13][14][15][16][17] Systematic work on the topic by Schuh, Nieh and their colleagues [8][9][10][11][12] demonstrated that the serrated (inhomogeneous) plastic flow of the BMG during nanoindentation is strongly dependent not only on chemical composition but also on indentation loading rate; the serrated flow is observed only at a slow loading rate and it gradually disappears with increasing loading rate.…”
Section: Introductionmentioning
confidence: 99%